"They Just Want The Best Person, The Most Normal Person": Comparing Women With Disabilities and Employers Perspectives on Service Work - Schuer, Stephanie (My University, 2005)
This thesis compares women with disabilities and employers' perspectives on service work in Hamilton, Ontario in order to further understand the experiences of disabled women in contemporary service employment. Positive and negative experiences from the women interviewed are assessed and compared to employers' perspectives on hiring and working with disabled workers in the service sector. With the recent restructuring of the welfare state, more disabled-people are being encouraged to enter the paid workforce by the state. This situation is problematic because there are indications that enduring barriers to employment continue to exist, and the restructuring of the service sector raises questions concerning the types of work people with disabilities are being hired for. Evidence from this thesis suggests that there is often a fundamental disconnect between what many employers are looking for in a worker and what the women interviewed were able to offer while at work. It can be suggested that "} both data sets point to the enduring norms of able-bodiedness in the workplace. This study suggests that the women are not always able to approximate what the employers construct as the ideal worker, however the women have created various coping strategies in order to best approximate the ideal. The type of emotional, embodied work that is required by the majority of the employers in the service sector can be physically and emotionally draining for women with disabilities. This research also suggests that different bodies experience different outcomes in different situations. The women interviewed made it clear that they experience their bodies differently at work than they would at home, because of the demanding nature of service work and the performative, emotional nature of their work. The research conducted in this thesis responds to the absence of studies comparing the perspectives of both women with disabilities experiences and employers perspectives on service work.
Keywords: Service Work; Disabilities